2020
DOI: 10.6026/973206300161051
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of systemic diseases in patients undergoing minor oral surgeries

Abstract: It is of interest to evaluate the prevalence of systemic disorders in patients undergoing minor oral surgeries at a dental hospital. This will help to take necessary precautions prior to oral surgeries. We used the digital case records of 1288 patients who underwent minor oral surgeries in a hospital. Demographic details and systemic diseases of the patients were recorded from digital case records. Data shows that 103 patients (7.9%) of the total number of patients undergoing minor oral surgeries had systemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
1
3
1
Order By: Relevance
“…The most commonly reported disease in our study was diabetes mellitus followed by hypertension, gastrointestinal, haematological and respiratory. Similar findings were reported by other studies (12,16) , but in contrast to numerous other studies which have reported hypertension is the most common (16)(17)(18) . In the present study, cardiovascular diseases (hypertension) came second as the most prevalent medically compromised conditions in dental patients, similar toother studies (19) .…”
Section: Discussionsupporting
confidence: 92%
“…The most commonly reported disease in our study was diabetes mellitus followed by hypertension, gastrointestinal, haematological and respiratory. Similar findings were reported by other studies (12,16) , but in contrast to numerous other studies which have reported hypertension is the most common (16)(17)(18) . In the present study, cardiovascular diseases (hypertension) came second as the most prevalent medically compromised conditions in dental patients, similar toother studies (19) .…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of psychiatric conditions in this study differs markedly from the results of the other studies that specifically examined patient medical profiles from oral surgery services in university settings, mainly in South Asia (Amado Cuesta et al, 2004;Kolte et al, 2014;Mahmood et al, 2020;Natarajan et al, 2019;Santhosh, 2020;Santhosh Kumar, 2021;Santhosh Kumar & Rajan, 2016;Siddiqi et al, 2016;Walia et al, 2017).…”
Section: Prevalencecontrasting
confidence: 87%
“…Studies examining the medical profiles of patients undergoing minor oral surgery procedures at university teaching settings have been carried out in South Asia (Kolte et al, 2014 ; Mahmood et al, 2020 ; Natarajan et al, 2019 ; Santhosh, 2020 ; Santhosh Kumar, 2021 ; Santhosh Kumar & Rajan, 2016 ; Siddiqi et al, 2016 ; Walia et al, 2017 ) and Western Europe (Amado Cuesta et al, 2004 ). To date, this is the first study in the southern hemisphere specifically investigating the prevalence of medical conditions and medication types in patients referred to postgraduate oral surgery students.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A situation is stressful when it is perceived by a person as threatening and uncontrollable and that person does not have the necessary resources to face the situation ( 12 ). Previous studies indicate that the statistics for anxiety and stress in patients undergoing surgery are significant ( 13 16 ); therefore, assessment and appropriate interventions are needed ( 17 20 ). The skills that an individual develops throughout their life, particularly cognitive and emotional skills that are acquired when individuals are facing stressful situations, play a crucial role in their ability to manage stress ( 21 ).…”
Section: Introductionmentioning
confidence: 99%